Examining the Evolution and Components of the Culture of Learning in University Education: A Systematic Scoping Review - Tatiana Laguttseva-Nogina; Nadezhda Arupova; Natalya Mekeko; Svetlana Fomina (National Research University Higher School of Economics, 2024)
Introduction: The term "culture of learning" frequently appears in research on educational development and reform, yet defining it precisely remains challenging. Given its varied interpretations across scientific fields, it is crucial to review how authors use "culture of learning" in the context of modern educational environments. Purpose: The purpose of this study is to comprehensively examine and map the existing literature on the concept of "culture of learning" within educational environments. Method: The research strategy for this scoping review was structured around the "problem, concept, and context (PCC)" framework to ensure a comprehensive and logical exploration of the literature. This approach facilitated the systematic identification and selection of relevant materials that provide a rationale for each chosen criterion. A detailed research protocol was established prior to initiating the study, outlining the objectives, inclusion criteria, and methodological approach. The reporting of this systematic scoping review adheres to the PRISMA-ScR (Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews) guidelines, ensuring transparency, rigor, and reproducibility in the review process. This methodology was selected to provide a clear and structured pathway for mapping the existing literature on the culture of learning, highlighting key themes, trends, and gaps within the field. Results: Upon reviewing 74 articles, we identified and clustered the most frequently occurring terms in the titles, resulting in the formation of five distinct area clusters. These clusters encompass: the effectiveness of teaching and learning processes (and their components); teaching/learning trends; learning styles and processes (and their components); learning model components; and the emphasis on academic literacy as an integral part of the learning culture. Additionally, components of the architecture of the culture of learning were identified: learning environments, learning groups, learning subcultures, learning approaches and methods, and learning values and traditions. This comprehensive analysis allowed to define and structure the components of the learning culture. Conclusion: This scoping review contributes to the ongoing efforts to understand the concept of the "culture of learning" by providing comprehensive definitions and analyzing its possible components. The results offer educators and policymakers a clearer understanding of what constitutes a culture of learning, enabling them to design and implement more effective educational strategies and policies. These findings can guide the development of curricula that better integrate various learning cultures, thereby enhancing the educational experience for students. By identifying key trends and components of the culture of learning, this review provides a foundation for further research that can explore new methodologies and approaches in education, ultimately leading to improved learning outcomes and more dynamic educational environments.